Research in No Traditional Fruit Crops at the Biotechnology Research Center of Costa Rica Institute of Technology - Schmidt-Durán, Alexander (2019)
The non-traditional fruit crop research team at the Biotechnology Research Center (CIB) of Costa Rica Institute of Technology (TEC) has engaged in the task of diversifying the country ́s agricultural offer, generating knowledge related to certain crops that have considerable commercial potential. Therefore, research studies related to fig, blackberry, quency, and tamarillo crops have been performed, including in vitro culture of the plant species; their agronomical management; plagues and diseases; molecular characterization of the plant species and their varieties; biological control; agroindustry and, most recently, in understanding the physiologic, pathologic, and metabolic processes of the plants, related to the defense mechanisms from pathogen attacks and the production of nutraceutical compounds of interest. The research team works in generating technological packages for farmers, in order to enhance the nationwide production of these crops.